Discrete Model of Wave Propagation in a Rod with Rigid Unloading Characteristic - Szcześniak, Z. (Engineering Transactions, 1992)
A principle of construction and action of a discrete model of a rod with rigid characteristic of unloading is proposed. Its applications are shown for loading that varies arbitrarily with time. Propagating waves in this case cause multiple effects of rigid unloading and reloading in each cross-section of the rod. These effects are highly nonlinear and very difficult to describe analytically. Numerical algorithm is given. Its effectiveness is demonstrated on an example and solution errors are discussed.